American scientists and their fictions: professional authorship and intellectual identity, 1870-1900 - Vandome, Robin (Cambridge University Press, 2017)
Writers and critics in the Gilded Age United States frequently debated the relations between literature and science. A common contemporary interpretation of this relationship held that these two ways of knowing and writing were fundamentally opposed and that the advancement of science in American culture came at the expense of literary sensibilities. Nevertheless, and often as an effort to challenge this supposed opposition, many scientists also cultivated reputations as literary figures, and produced or planned diverse works ranging from travel-writing and novels to verse drama. Such authors as Clarence King, J. Peter Lesley, Simon Newcomb and Nathaniel Southgate Shaler sustained a hybrid literary-scientific culture in the late nineteenth-century. This interdisciplinary cultural zone was fragile and increasingly fractured by around 1900, as the emergence and consolidation of new categories of intellectual labour became increasingly wedded to the images of the “professional author” and the “scientist” as mutually exclusive identities. This article seeks to contribute to recurrent debates about the “two cultures” of literature and science by foregrounding the differentiation of these new forms of professional and intellectual identity as a decisive factor which constrained the possibility of a shared literary-scientific culture by the turn of the twentieth century.